Use of qualitative research in foodservice organizations: a review of challenges, strategies, and applications - Arendt, Susan W.; Roberts, Kevin R.; Strohbehn, Catherine; Ellis, Jason D.; Paez, Paola; Meyer, Janell (My University, 2012)
Purpose – The purpose of this paper is to present the challenges encountered when conducting qualitative research in foodservice operations and to discuss the strategies to overcome the identified challenges. Design/methodology/approach – The researchers conducted food safety observations, interviews, and focus groups with more than 600 foodservice employees and managers. The researchers encountered multiple challenges including institutional review board approvals, managements’ willingness to participate, and organizational and cultural barriers. Findings – Obtaining in-depth, credible information through observations, interviews, and focus groups adds depth and breadth to hospitality studies. However, given high industry turnover, recruitment and retention throughout a study is problematic. Moreover, researchers encounter many barriers as they obtain data, such as establishing authenticity and overcoming Hawthorne and halo effects. Originality/value – Strategies to increase participation and thereby improve qualitative research have not been previously addressed in the hospitality literature
Keywords: Focus groups; Food safety; Foodservice; Interviews; Observations; Qualitative research